Learning assistance and growing a clean and healthy lifestyle for elementary school students in Nusupan, Salaman, Magelang, Indonesia - Wijayanto, Sukma; Khusna, Adil Latal; Indriastuti, Yayuk; Nisa’, Nur Ifany Choirun; Khusniah, Anisatul; Sadewa, Refri Rais (Community Empowerment, 2021)
In order to minimize the spread of Covid-19, students must learn from home. However, studying from home online is often ineffective. In addition, the existence of Covid-19 requires awareness of a healthy lifestyle. This activity aims to help the learning process from home and growing Clean and Healthy Behavior (PHBS) in elementary school students. Methods of problem solving were carried out by socialization, training, and assistance to partners. Activities carried out include hand washing practices, socialization about Covid-19, training in making hand sanitizers, face shields, and tie dye masks. Furthermore, this activity was able to optimize the learning process from home and form a new awareness of the importance of clean and healthy living habits.